Linking Macro and Regional Level Economic Forecasts: Alternative Regional Growth Paths in Hungary - Zsuzsanna Zsibók (DETUROPE)
Economic development at the national level is often accompanied by territorial divergence at sub-national levels, which phenomenon became even more noticeable during and after the global financial and economic crisis. Current development policy have to face the well-known equity versus efficiency challenge to sustain the prosperity of the most advanced regions and, at the same time, to tackle the divergence between advanced and lagging regions. For this reason, a comprehensive knowledge is necessary about the long-run, interdependent dynamics of national and regional level growth. Our research contributes to this knowledge through studying alternative growth paths for Hungary in a comparative framework. We focus on the methods that apply a regionalisation procedure in order to downscale national level economic forecasts to the regional level.